SELECTED CHALLENGES AFFECTING THE RETROACTIVE TRANSFER PRICING ADJUSTMENTS OF IMPORTED GOODS IN SOUTH AFRICA - Howard Chitimira; Oratile Maselwa (Obiter, 2021)
The article analyses selected challenges associated with retroactive transfer pricing adjustments of imported goods under the Customs and Excise Act 91 of 1964 (Customs and Excise Act). This is done in order to examine the regulatory challenges affecting retroactive transfer pricing adjustments and customs valuation processes of imported goods under the Customs and Excise Act. Thus, the enforcement of retroactive transfer pricing adjustments of imported goods for Multinational Enterprises (MNEs) is scrutinised in terms of the Customs and Excise Act. To this end, the article provides an overview analysis of selected regulatory and related challenges affecting retroactive transfer pricing adjustments and actual valuation processes of imported goods within different MNEs in South Africa. Accordingly, the article explores selected challenges in order to recommend possible remedies and measures that could be employed by policy makers to enhance the regulatory and enforcement framework under the Customs and Excise Act.